2020
DOI: 10.31234/osf.io/t9kds
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A randomised control trial to evaluate messages that promote limit setting and the impact of limits on online gambling behaviour

Abstract: Background & Aim: Deposit limits may be an effective strategy for minimising the harm associated with online gambling. However, voluntary uptake of these tools is low. This study aimed to compare the effectiveness of different messages to increase use of deposit limits by customers of online gambling sites and to examine the effects of limit setting on gambling behaviour. Design: A pre-registered, naturalistic randomised control trial was conducted wherein customers were sent varied messages by online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The development of strategies for effectively communicating the potential benefits of timeouts is particularly warranted given the very low uptake rates and dearth of research on the promotion of tools other than limits. We found that an opt-out limit scheme substantially increased deposit limit use which, in conjunction with the finding of responsible gambling messaging studies (e.g., Heirene & Gainsbury, 2020), suggests strategies that reduce the effort required for customers to access and utilize CPTs may be useful for encouraging their use. We identified a key limitation of the deposit limit tool currently offered on Australian sites (i.e., the ability to easily increase limits multiple times or remove them altogether) which supports the introduction of greater friction and delays to increase limits and messaging to assist customers to determine, set, and adhere to appropriate limits.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…The development of strategies for effectively communicating the potential benefits of timeouts is particularly warranted given the very low uptake rates and dearth of research on the promotion of tools other than limits. We found that an opt-out limit scheme substantially increased deposit limit use which, in conjunction with the finding of responsible gambling messaging studies (e.g., Heirene & Gainsbury, 2020), suggests strategies that reduce the effort required for customers to access and utilize CPTs may be useful for encouraging their use. We identified a key limitation of the deposit limit tool currently offered on Australian sites (i.e., the ability to easily increase limits multiple times or remove them altogether) which supports the introduction of greater friction and delays to increase limits and messaging to assist customers to determine, set, and adhere to appropriate limits.…”
Section: Discussionsupporting
confidence: 65%
“…However, before deciding which CPTs should be implemented via an opt-out system or encouraged via messaging it is important that future studies evaluate the harm-reducing qualities of new and existing CPTs on online sites as quality trials are scant (cf. Heirene & Gainsbury, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations